Panayiotopoulos Syndrome: Benign Autonomic Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2006)
The clinical features, EEG, misdiagnoses, and management of children with Panayiotopoulos syndrome (PS) are reviewed from Sophia Children's Hospital, Goudi-Athens, Greece.